Circulating myeloid populations have prognostic utility in alcohol-related liver disease - Khan, Reenam; Salman, Shees; Harford, Laura; Sheriff, Lozan; Hazeldine, Jon; Rajoriya, Neil; Newsome, Philip N.; Lalor, Patricia F. (Frontiers in Immunology, 2024)
Introduction Alcohol-related liver disease (ARLD) accounts for over one third of all deaths from liver conditions, and mortality from alcohol-related liver disease has increased nearly five-fold over the last 30 years. Severe alcohol-related hepatitis almost always occurs in patients with a background of chronic liver disease with extensive fibrosis or cirrhosis, can precipitate ‘acute on chronic’ liver failure and has a high short-term mortality. Patients with alcohol-related liver disease have impaired immune responses, and increased susceptibility to infections, thus prompt diagnosis of infection and careful patient management is required. The identification of early and non-invasive diagnostic and prognostic biomarkers in ARLD remains an unresolved challenge. Easily calculated predictors of infection and mortality are required for use in patients who often exhibit variable symptoms and disease severity and may not always present in a specialized gastroenterology unit. Methods We have used a simple haematological analyser to rapidly measure circulating myeloid cell parameters across the ARLD spectrum. Results and Discussion We demonstrate for the first time that immature granulocyte (IG) counts correlate with markers of disease severity, and our data suggests that elevated counts are associated with increased short-term mortality and risk of infection. Other myeloid populations such as eosinophils and basophils also show promise. Thus IG count has the potential to serve alongside established markers such as neutrophil: lymphocyte ratio as a simply calculated predictor of mortality and risk of infectious complications in patients with alcohol-related hepatitis. This would allow identification of patients who may require more intensive management.